Implementasi Maqashid Syariah dalam Merumuskan Tujuan Laporan Keuangan Bank Syariah - Habibah, Muzayyidatul (IAIN Kudus, 2020)
This research aims to analyze how the implementation of maqashid as-sharia in formulating Islamic bank financial statements’ objectives. The research method used is a descriptive qualitative approach, through field research, by examining published Islamic financial reports and conducting interviews with management. The purpose of preparing Islamic financial reports on Islamic entities following the maqashid as-sharia is to fulfil the objectives in providing useful information to stakeholders comprehensively. The purpose of Islamic financial reports includes three levels, namely primary (dharuriyat), secondary (tahsiniyah), and tertiary (hajiyat). The primary aspect is very useful in providing financial information that all financial institutions' activities come from halal sources. Meanwhile, the second aspect can provide additional information on adherence to sharia principles, as a form of protection for property development through contracts under sharia principles. In the aspect of fulfilling the tertiary level, it shows the urgency in presenting assets owned by sharia entities in a transparent and accountable manner, as an effort to be accountable to humans and Allah SWT., Thus providing benefits to more people. Fulfillment of these three aspects of maqashid sharia is a form of benefit in the management of sharia entities.